A Systematic Review of the Clinimetric Properties of Habitual Physical Activity Measures in Young Children with a Motor Disability. (9th August 2012) - Oftedal, Stina; Bell, Kristie L.; Mitchell, Louise E.; Davies, Peter S. W.; Ware, Robert S.; Boyd, Roslyn N.
Abstract : Aim . To identify and systematically review the clinimetric properties of habitual physical activity (HPA) measures in young children with a motor disability. Method . Five databases were searched for measures of HPA including: children aged <6.0 years with a neuromuscular disorder, physical activity defined as "bodily movement produced by skeletal muscles causing caloric expenditure", reported HPA as duration, frequency, intensity, mode or energy expenditure, and evaluated clinimetric properties. The quality of papers was assessed using the COSMIN-checklist. A targeted search of identified measures found additional studies of typically developing young children (TDC). Results . Seven papers assessing four activity monitors met inclusion criteria. Four studies were of good methodological quality. The Minimod had good ability to measure continuous walking but the demonstrated poor ability to measure steps during free-living activities. The Intelligent Device for Energy Expenditure and Activity and Ambulatory Monitoring Pod showed poor ability to measure activity during both continuous walking and free-living activities. The StepWatch showed good ability to measure steps during continuous walking in TDC. Interpretation . Studies assessing the clinimetric properties of measures of HPA in this population are urgently needed to allow assessment of the relationship between HPA and health outcomes in this group.